2017
DOI: 10.3945/ajcn.116.146761
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary nitrate with atherosclerotic vascular disease mortality: a prospective cohort study of older adult women

Abstract: Background: Nitrate-rich vegetables lower blood pressure and improve endothelial function in humans. It is not known, however, whether increased consumption of nitrate-rich vegetables translates to a lower risk of atherosclerotic vascular disease (ASVD) mortality. Objective: The objective was to investigate the association of nitrate intake from vegetables with ASVD mortality. Design: A total of 1226 Australian women aged 70-85 y without prevalent ASVD and/or diabetes were recruited in 1998 and were studied fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 35 publications
8
75
1
Order By: Relevance
“…Blekkenhorst et al (21) were the first to investigate prospectively the association of dietary nitrate (measured only at baseline) with atherosclerotic vascular disease (ASVD) mortality including ischaemic heart disease, heart failure, cerebrovascular disease (excluding haemorrhagic stroke) and peripheral arterial disease, in 1226 Australian women aged 70-85 years, followed up for 15 years. Finding from Blekkenhorst et al (21) indicated that participants in the highest (>76•4 mg/d) compared with the lowest (<52•7 mg/d) tertile of total vegetable nitrate intake had a lower risk of ASVD (21) . Within the same cohort, Bondonno et al (41) found that for every 1SD (31 mg/d) higher intake of total nitrate, there was an associated 18 % lower risk of 14•5-year ischaemic cerebrovascular disease events (P = 0•017).…”
Section: Discussionmentioning
confidence: 99%
“…Blekkenhorst et al (21) were the first to investigate prospectively the association of dietary nitrate (measured only at baseline) with atherosclerotic vascular disease (ASVD) mortality including ischaemic heart disease, heart failure, cerebrovascular disease (excluding haemorrhagic stroke) and peripheral arterial disease, in 1226 Australian women aged 70-85 years, followed up for 15 years. Finding from Blekkenhorst et al (21) indicated that participants in the highest (>76•4 mg/d) compared with the lowest (<52•7 mg/d) tertile of total vegetable nitrate intake had a lower risk of ASVD (21) . Within the same cohort, Bondonno et al (41) found that for every 1SD (31 mg/d) higher intake of total nitrate, there was an associated 18 % lower risk of 14•5-year ischaemic cerebrovascular disease events (P = 0•017).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also indicated a non-linear association between dietary nitrate and vascular disease mortality, with the largest benefits observed among those with moderate nitrate intakes which is consistent with our data. 13 Alternatively, the small number of incident AMD cases could have reduced power to detect a modest association at the highest intake quartiles. Moreover, we observed no significant associations with incidence of late AMD, again this is likely to be due to the small number of incident late AMD cases (~4%), compared to ~15% incidence of early AMD cases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed no significant associations between non-vegetable nitrate intake and incidence of early or late AMD, this is not surprising given that there is no clear consensus on the impacts on health after consumption of non-vegetable sources of dietary nitrate. 13 Inflammation, oxidative stress, and endothelial dysfunction are among the many factors that are hypothesized to influence the incidence and progression of AMD. 2,6 Given that nitrate intake, particularly from vegetable sources, was previously shown to improve endothelial function and minimize oxidative stress, 4 this is a potential pathway by which dietary nitrate intake could protect against early AMD.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed overall diet quality using the Nutrient‐Rich Foods Index . This index was calculated using the Nutrient Reference Values for Australia and New Zealand based on adult women older than 70 years and has been previously described …”
Section: Methodsmentioning
confidence: 99%